Analisis Perbandingan Lampu LED dan Halogen pada AFL (Airfield Lighting System) Bandar Udara Rendani Manokwari: Analysis of LED and Halogen Lights Comparisonat AFL (Airfield Lighting System) Rendani Manokwari Airport - Riyanto Fajrul Ramadhan; Pandung Sarungallo; Rio O. Pramanegara (JISTECH: Journal of Information Science and Technology, 2025)
The AFL (Airfield Lighting System) is a crucial part of the airport infrastructure that plays an important role in supporting aircraft operations. Using LED type lights allows for more efficient energy use and has a longer service life. Of course this would be an effective solution to dealing with energy waste. In this study this time will discuss the comparison of light intensity, and comparison efficiency of electric energy use of LED lamps with halogen lamps at Manokwari Rendani Airport, and Comparison of the cost of electricity consumer of LED light to halogen light at Manokwari rendani Airport. The power of the halogen lamps is 2.239.25 cd, while the light of the LED lamps with a reflection factor of 0.98 is 6.539.05 cd. This results in a threefold comparison between the alpha taxiway and the bravo taxiway. The use of halogen lights costs Rp. 3.557.429,28 per year, whereas the use of LED lights requires electricity costs of Rp 1.185.809,76 per year. You can see that the use of bravo taxiway lamps with LED type is more efficient in terms of energy consumption, light intensity and cost effectiveness compared to alpha taxiway lights with halogen type